Ritmanálise em Santa Tereza: modos de vida urbana - Ana Beatriz Mascarenhas Pereira (2017)
The protection of the Santa Tereza neighborhood by the Municipality of Belo Horizonte as cultural heritage originated the production of this Masters thesis. The Dossier for the Protection of the Urban Complex Santa Tereza Neighborhood was the stimulus for the research in so far as it is based on the ways of life as its main characteristic. In this sense, the rhythmanalysis provides a very convenient methodology to corroborate the merit of the protection of the neighborhood. Coined by the mathematician, physicist and philosopher Lúcio Pinheiro dos Santos and developed years later by the philosopher Henri Lefebvre, in his work Éléments de rythmanalyse, rhythmic analysis seeks to investigate the individual and social rhythms in certain temporal and spatial cuts. In addition, the work of Jane Jacobs - Death and life of great american cities, has contributed to ratify the relevance of daily life in maintaining the liveliness of neighborhoods. The dissertation used bibliographical sources, documentary surveys in institutional archives besides interviews, informal conversations and participant observation.